Developing a process in evaluating human comfort in high-rise buildings using wind vibration responses - Mendoza, Jasper Ian B.
The Philippines experience about 20 typhoons a year, these typhoons have strong winds that may cause high-rise buildings to vibrate, due to their inherent low natural frequencies. These vibrations may cause some discomfort to the building occupants that may affect their work, cause fear or alarm and induce symptoms of motion sickness. The objective of this research is to come up with an efficient method in assessing human comfort, based on related literatures. Survey forms were used to assess the need to include human comfort in the design of buildings in the country. Results give high percentage of respondents that felt building motion (77.22%) and these have judged the motion to be unpleasant. A computer software, namely SAP2000 and an equation proposed by Lagomarsino was used to obtain ilie natural frequency of the building. Using the proposed method, and the computed natural frequencies, accelerations due to different wind speeds from Storm Signals were obtained for a building with varying height. The obtained accelerations were compared to published comfort criterion from IS010137 and IS06897. The building fails botll criterion for winds exceeding the maximum speed of a Signal #2 Typhoon, however, using frequency from SAP2000 the building fails the criterion for only Signal #1 winds. Finally, accelerations of the building with 60 floors for ambient wind speed, were computed using equations given by the Eurocode EN 1991-1-4, and the results of the proposed method were compared. The difference were small enough, 7.89% for computations using SAP2000 and 10.67% using Lagomarsino frequencies, to conclude that the proposed method is valid. Also since the standards themselves have stated that their criterion is more of a perception limit and that comfort varies greatly between individual, it was concluded that the use of survey questionnaires is an essential part in assessing human comfort.